ADVANCING VOCATIONAL EDUCATION WITH VOCAR-FLIP: IMPROVING STUDENT COMPREHENSION IN THE DIGITAL ERA - Asri Wibawa Sakti; Sri Rahayu; M. Muktiarni; Zahra Ghinaya; Zenita Sabitri (Jurnal Pensil)
In the 21st century, globalization and digital transformation have changed life patterns significantly. Digital technology is now at the center of almost all aspects of life, including the education sector in Indonesia. Technological skills and readiness to face the job market demands are critical. Vocational education, including vocational schools, aims to equip students for global market competition but continues to encounter obstacles in enhancing the quality and relevance of its programs. The proposed solution is the development of flipbook- based learning media with Augmented Reality (AR) to increase student engagement and skills in this digital era. This study employed a pre-experimental design with a one-group pretest-posttest approach, involving a population of 149 vocational school students from West Java. The research results show that using Flipbook with AR produces an N-gain score of 74.3%. With this N-gain value, the VocAR-Flip model effectively improves vocational school students' learning outcomes, especially in academic achievement and conceptual understanding. This research can contribute to developing more interactive and efficient learning technology for future education.